Awareness of Consumer Protection Act among Doctors in Udaipur City, India - S. Shetty; K. Singh; N. Bhat; A. Sharda; A. Agrawal; H. Chaudhary (Tehran University of Medical Sciences, 2010)
Objective: To compare the awareness of provisions of consumer protection act among dental and medical professionals in Udaipur city, Rajasthan, India. Materials and Methods: In a cross sectional study, a total of 448 professionals (253 males, 195 females) belonging to dental (222) and medical (226) categories were surveyed using a self administered structured questionnaire. The questionnaire comprised of 22 questions about the awareness of consumer protection art (CPA) and whether these professionals were following the recommendations of CPA. The student's t-test, ANOVA test, and Scheffe's test were used as tests of significance. Results: The awareness scores were significantly higher for medical professionals compared with those of dental professionals. Similarly, postgraduates showed more awareness in both the professions and it was found that private practitioners significantly have more awareness than the academic sector. Conclusion: Though medical professionals have more awareness of CPA compared to dental professionals, considering the present scenario, better knowledge of CPA is necessary for both professionals in order to be on the safer side.